Những quan điểm cơ bản của C.Mác, F.ĂngGhen, V.I.Lê Nin, Hồ Chí Minh và Đảng ta về giai cấp và liên minh giai cấp trong thời kỳ quá độ lên CNXH : Đề tài NCKH. CB.01.35 - Phạm, Ngọc Thanh (H. : ĐHQGHN, 2017)
155 tr.